THE RELATIONSHIP STUDY OF TEACHER’S PERCEPTION ON THEIR LEADERSHIP CAPACITY AND TEACHING COMPETENCE AT BAOSHAN EXPERIMENTAL SCHOOL, SHANGHAI, CHINA - CUI, YEHONG; YE, YAN (Scholar: Human Sciences, 2022)
The primary purpose of this research study was to determine the relationship between teachers’ perceptions of their leadership capacity and competence at Baoshan Experimental School, Shanghai, China. The research instrument was a questionnaire for investigating the teachers’ perceptions of their leadership capacity and competence adopted from the previous studies. A total of 120 teachers who were full-time teachers working at the school participated in this study during the academic year of 2020. Mean and Standard Deviation were used to identify teachers’ perceptions of their leadership capacity and determine teachers’ level of competence. Then, Pearson’s Product Moment Correlation Coefficient was then used to determine the significant relationship between teachers’ perceptions of leadership capacity and their competence. The findings showed that teachers’ perceptions of their leadership capacity and professional competence were high. Moreover, the correlation analysis result showed a strong positive relationship between teachers’ perceptions of their leadership capacity and competence at Baoshan Experimental School, Shanghai, China.